Electron Kinetics in Dye Sensitized Solar Cells Employing Anatase with (1 0 1) and (0 0 1) Facets. (1st April 2015) - Laskova, Barbora; Moehl, Thomas; Kavan, Ladislav; Zukalova, Marketa; Liu, Xianjie; Yella, Aswani; Comte, Pascal; Zukal, Arnost; Nazeeruddin, Mohammad Khaja; Graetzel, Michael
Highlights: Electrochemical impedance spectroscopy and transient photovoltage/photocurrent decay indicate larger chemical capacitance of (0 0 1)-oriented TiO2 anatase nanosheets compared to ordinary (1 0 1)-terminated crystals. Larger density of deep electron traps in the (0 0 1)-oriented TiO2 anatase nanosheets is confirmed by optical and photoemission spectra. Electrons in the (0 0 1)-oriented TiO2 anatase nanosheets show higher lifetime and slower diffusion. Abstract: Two phase-pure nanocrystalline anatase materials differing in the exposed crystal facets (0 0 1) or (1 0 1) are studied by electrochemical impedance spectroscopy and by transient photovoltage and photocurrent decay in dye sensitized solar cells. A larger chemical capacitance, indicating larger density of states, is observed for anatase (0 0 1). The presence of deep electron traps in (0 0 1) nanosheets is further confirmed by optical (UV-Vis) and photoemission (XPS, UPS) spectra. The difference in chemical capacitance indicates a slower diffusion of electrons in the (0 0 1) anatase material, but also a higher electron lifetime compared to (1 0 1) anatase material.